2015
DOI: 10.1186/s12906-015-0934-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of an antifungal compound 5-hydroxy-7,4’-dimethoxyflavone from Combretum zeyheri

Abstract: BackgroundCombretum zeyheri, belongs to the family Combretaceae and is one of the most popular herbal plants in tropical and subtropical countries. The leaves of Combretum zeyheri have been used as herbal medicine and have been reported to have pharmacological activity which includes anti-bacterial, anti-fungal, anticancer and antioxidant properties. The goal of this study was to isolate, identify and characterize compounds from C. zeyheri leaves which are responsible for its antifungal activity.MethodsThe pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 18 publications
(19 reference statements)
2
19
0
Order By: Relevance
“…This study showed that C. zeyheri possesses antifungal activity against Candida albicans and this is in agreement with other previous studies [ 18 20 ]. The ethanol extract, alkaloid, saponin and flavonoid-enriched fractions exhibited antifungal activity.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This study showed that C. zeyheri possesses antifungal activity against Candida albicans and this is in agreement with other previous studies [ 18 20 ]. The ethanol extract, alkaloid, saponin and flavonoid-enriched fractions exhibited antifungal activity.…”
Section: Discussionsupporting
confidence: 94%
“…In this study the alkaloids, flavonoids and saponins were extracted as a preliminary step towards identifying the specific active constituents. Indeed it has been shown that the flavonoid 5-hydroxy-7,4’-methoxyflavone isolated from C. zeyheri had antifungal effects [ 20 ]. The MIC of the positive control, miconazole was as expected and was found to be at 6.25 μg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…At the determined time, an aliquot of 30 µL was taken from each test suspension and inoculated into SDA for quantifying the colony forming units. Sabaroud dextrose broth (SDB) without any antifungal agent was used as a control [25].…”
Section: Time-kill Assaysmentioning
confidence: 99%
“…Leaves, stem bark and fruits of both species presented antifungal activity against different Candida spp. (Cock and Van Vuuren, 2015;Fyhrquist et al, 2004;Mangoyi et al, 2015;Masoko et al, 2007;Mutasa et al, 2015;Runyoro et al, 2013). Antiinflammatory activities (inhibition of hematopoietic prostaglandin D2 synthase) were detected in leaves of both species (Chimponda and Mukanganyama, 2015;Eloff et al, 2001;McGaw et al, 2001).…”
Section: Combretaceaementioning
confidence: 96%